Alkyl Radical Generation by an Intramolecular Homolytic Substitution Reaction between Iron(II) and Trialkylsulfonium Groups. Issue 43 (18th July 2018) - Jungen, Stefan; Chen, Peter
Abstract: Invited for the cover of this issue are Peter Chen and Stefan Jungen at the Eidgenössische Technische Hochschule (ETH) in Zürich. The image depicts a table‐top firework with the tip of an ion guide used in mass spectrometers that spits out the products of a homolitic substitution reaction between iron(II) and trialkylsulfonium species. Read the full text of the article at10.1002/chem.201801952 . Abstract : " The geometric environment around the iron(II) seems to be crucial for this homolytic substitution reaction to occur ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 11008 ff. (DOI:10.1002/chem.201801952 ).